Ruínas da contemporaneidade. Tempelhof na transformação urbana de Berlim. - Nadia Martins Pinheiro Santos (2013)
The following paper aims to study the issue of re-appropriation and rehabilitation/renewal of empty equipments/spaces related to a process of uncertainty considering the urban tissue of the contemporary city. By studying the process of transformation of the former Berlin airport, Tempelhof, this transformation and reinterpretation of spaces, taking into account closer approaches in response to society's interests. urban transformation of the city where it is located, Berlin, with a special framework to plan while process, framed in the tradition of urban transformation in Berlin.